Symposium 2: Enhancing Learner Progression (ELP): Understanding the Learners' Perspectives: Symposium Introduction - Higgison, Carol; Currant, Neil; Murray, Christopher; Pellow, Andy; Taylor, Jill; Hairsine, James; Hennessy, Scott; Raby, Sally; Sykes, Rebecca (Proceedings of the International Conference on Networked Learning, 2006)
The rapid expansion of use of e-Portfolios in support of learning and teaching in all education sectors in the UK is being driven by a range of government policies (Beetham, 2005) that are based on the premise that progress files (portfolios) can make the outcomes of lifelong learning more explicit to the learner, their tutors and employers (Universities UK, 2003) thus increasing aspiration and attainment. This JISC funded Enhancing Learner Progression (ELP) project aims to evaluate the application and potential of e-portfolios in supporting learners through their lifelong learning journey by examining ways that e-portfolios can provide learners support at key transition points in this journey, in particular, from school and Further Education (FE) into Higher Education (HE) and from HE into professional practice. The focii of this symposium are the extent to which the learners’ experiences match this policy ideal at these two key transfer points in the learning journey and improving our understanding of the factors that impact on their experiences through an examination of other stakeholder perspectives.